Baleen Whale Occurrence in the Waters Off Virginia and North Carolina, U.S.A. From 2001 to 2019 - Sarah D. Mallette; William A. McLellan; D. Ann Pabst; M. Louise Burt; Ryan J. McAlarney; Gwendolyn G. Lockhart; Erin W. Cummings; Joel T. Bell; Matthew B. Ogburn; Philip K. Hamilton; Andrew J. Read; Robert L. Brownell; et al. (Marine Mammal Science, 2026)
Eighteen years of visual survey and strandings data were used to describe baleen whale occurrence along the continental shelf of Virginia and North Carolina, U.S.A. This region experiences heavy anthropogenic use, which poses risks for mortality and injury to baleen whales. Between 2001 and 2019, six species of baleen whales were recorded, and whales occurred year‐round. The total number of (on‐ and off‐effort) sightings and strandings amounted to 838 whales, including humpback ( Megaptera novaeangliae , n = 503) , fin ( Balaenoptera physalus , n = 197) , North Atlantic right ( Eubalaena glacialis , NARW, n = 76 ), common minke ( B. acutorostrata , n = 51), sei ( B. borealis , n = 10), and blue ( B. musculus , n = 1) whales. Spatial modeling and abundance estimates indicated whale density and distribution changed seasonally. The highest densities of all whales combined occurred in winter and spring. Across seasons, average densities were highest in the northern portion of the study area. Ninety percent of NARW sightings were outside the designated Seasonal Management Areas in place for their protection. The stranding record offered a complementary view of species richness and seasonality. This study provides a baseline of baleen whale occurrence in an area experiencing increasing anthropogenic pressures (e.g., ship traffic and offshore wind‐energy development).

Congener Conflict: Invasive Barred Owl Landscape Use Across the Range of the Northern Spotted Owl - Julianna M. A. Jenkins; Natalie M. Rugg; Raymond J. Davis; Scott A. Gremel; Aaron Henderson; Edward Henson; Mark Higley; Holly D. Horan; Christopher McCafferty; Thomas Munger; David Press; Suzanne Reffler; et al. (Journal of Biogeography, 2025)
Aim To map the probability of landscape use of invading barred owls ( Strix varia ) across the range of the threatened northern spotted owl ( S. Occidentallis Caurina ) in the Pacific Northwest, USA , identifying environmental drivers of barred owl landscape use to inform targeted management interventions. Location Forests of the Pacific Northwest, USA. Taxon Barred Owl ( Strix varia ). Methods We deployed 4081 autonomous recording units ( ARUs ) within 1027 randomly selected long‐term monitoring sites consisting of 5‐km 2 hexagons in 2023. We processed audio recordings using convolutional neural networks to detect vocalisations. We applied single‐season occupancy models at both ARU station and hexagon scales to estimate barred owl landscape use and assess associations with environmental variables. Using top models, we mapped barred owl landscape use across the full US range of the northern spotted owl, an umbrella species for conservation of the pacific northwest old‐growth forest community. Results Barred owls were widely detected, with naïve occupancy at 86.8% at the 5‐km 2 hexagon scale. We observed regional variation, with the highest landscape use in the Oregon Coast region and lower landscape use in California regions and the Washington Eastern Cascades. Landscape use was positively associated with mature forest characteristics at both broad and fine scales and negatively associated with elevation and climatic water deficit. Cumulative detection probability exceeded 90% after 2 weeks at the hexagon scale and 4 weeks at the station scale, providing guidance for future barred owl monitoring efforts. Main Conclusions Our study reveals extensive, but not ubiquitous, barred owl distribution across the range of the northern spotted owl. The findings offer a decision‐support framework for prioritising targeted management actions, particularly in regions with lower rates of barred owl landscape use. The integration of passive acoustic monitoring and AI‐based detection demonstrates a scalable approach for invasive species monitoring and conservation planning to meet management objectives in dynamic forest landscapes.

The role of serine/threonine protein phosphatase type 5 (PP5) in the regulation of stress-induced signaling networks and cancer - Teresa Golden; Mark Swingle; Richard E. Honkanen (Cancer and Metastasis Reviews, 2008)

Natal homing in juvenile loggerhead turtles ( Caretta caretta ) - BRIAN W. BOWEN; ANNA L. BASS; SHAIO‐MEI CHOW; MEREDITH BOSTROM; KAREN A. BJORNDAL; ALAN B. BOLTEN; TOSHINORI OKUYAMA; BENJAMIN M. BOLKER; SHERYAN EPPERLY; ERIN LACASELLA; DONNA SHAVER; MARK DODD; et al. (Molecular Ecology, 2004)
Juvenile loggerhead turtles ( Caretta caretta ) from West Atlantic nesting beaches occupy oceanic (pelagic) habitats in the eastern Atlantic and Mediterranean, whereas larger juvenile turtles occupy shallow (neritic) habitats along the continental coastline of North America. Hence the switch from oceanic to neritic stage can involve a trans‐oceanic migration. Several researchers have suggested that at the end of the oceanic phase, juveniles are homing to feeding habitats in the vicinity of their natal rookery. To test the hypothesis of juvenile homing behaviour, we surveyed 10 juvenile feeding zones across the eastern USA with mitochondrial DNA control region sequences ( N = 1437) and compared these samples to potential source (nesting) populations in the Atlantic Ocean and Mediterranean Sea ( N = 465). The results indicated a shallow, but significant, population structure of neritic juveniles (Φ ST = 0.0088, P = 0.016), and haplotype frequency differences were significantly correlated between coastal feeding populations and adjacent nesting populations (Mantel test R 2 = 0.52, P = 0.001). Mixed stock analyses (using a Bayesian algorithm) indicated that juveniles occurred at elevated frequency in the vicinity of their natal rookery. Hence, all lines of evidence supported the hypothesis of juvenile homing in loggerhead turtles. While not as precise as the homing of breeding adults, this behaviour nonetheless places juvenile turtles in the vicinity of their natal nesting colonies. Some of the coastal hazards that affect declining nesting populations may also affect the next generation of turtles feeding in nearby habitats.

LOCAL ABUNDANCE AND DISTRIBUTION OF BOTTLENOSE DOLPHINS ( TURSIOPS TRUNCATUS ) IN THE NEARSHORE WATERS OF VIRGINIA BEACH, VIRGINIA - Susan G. Barco; W. Mark Swingle; William A. Mlellan; Reid N. Harris; D. Ann Pabst (Marine Mammal Science, 1999)
A bstract We investigated patterns of abundance and distribution for coastal migratory Atlantic bottlenose dolphins ( Tursiops truncatus ) that appear seasonally in the nearshore waters of Virginia Beach, Virginia. The study was conducted along 24 km of shoreline at the southern point of the Chesapeake Bay mouth from April 1994 to March 1995. This is the first study to investigate the relationship between the abundance of coastal migratory dolphins and factors that might affect their movement. A profile analysis of variance revealed significant differences in local abundance and distribution throughout the year. Dolphin number was positively correlated with water temperature and not correlated with photoperiod. Although prey distribution and abundance are two factors thought to affect dolphin presence, in this study the relationship between these two factors and dolphin abundance was unclear. Greater numbers of dolphins were found in the ocean section of the study area. However, significantly higher ratios of neonatal dolphins were observed in the bay section, suggesting the bay serves as a nursery area. The observed relationship between local dolphin abundance and environmental factors in Virginia may provide insight into dolphin distribution and migration along the Atlantic coast of the United States.